2016
DOI: 10.1002/mrm.26548
|View full text |Cite
|
Sign up to set email alerts
|

Modeling diffusion of intracellular metabolites in the mouse brain up to very high diffusion‐weighting: Diffusion in long fibers (almost) accounts for non‐monoexponential attenuation

Abstract: The non-monoexponential signal attenuation of intracellular metabolites in the mouse brain can be described by diffusion in long and thin cylinders, yielding realistic D and fiber diameters. However, this simple model may require small "corrections" for NAA, in the form of a small fraction of the NAA signal originating from a highly restricted compartment. Magn Reson Med, 2016. © 2016 International Society for Magnetic Resonance in Medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
95
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(103 citation statements)
references
References 34 publications
8
95
0
Order By: Relevance
“…(Palombo et al, 2017) have also demonstrated diffusion of NAA and other metabolites can be modelled as occurring in long, cylindrical fibers, having a D a,‖ of 0.33 µm 2 /ms. The diffusion weighted signals of other metabolites were also fit well by assuming long cylindrical processes (Najac et al, 2016; Najac et al, 2014; Palombo et al, 2017). Since metabolites have differences in molecular size, affinity to charged surfaces, and potential ambiguity in compartment selectivity, the intra-axonal diffusivity of water cannot be unequivocally extrapolated from metabolite diffusivities.…”
Section: Validating Diffusion Modelsmentioning
confidence: 93%
See 1 more Smart Citation
“…(Palombo et al, 2017) have also demonstrated diffusion of NAA and other metabolites can be modelled as occurring in long, cylindrical fibers, having a D a,‖ of 0.33 µm 2 /ms. The diffusion weighted signals of other metabolites were also fit well by assuming long cylindrical processes (Najac et al, 2016; Najac et al, 2014; Palombo et al, 2017). Since metabolites have differences in molecular size, affinity to charged surfaces, and potential ambiguity in compartment selectivity, the intra-axonal diffusivity of water cannot be unequivocally extrapolated from metabolite diffusivities.…”
Section: Validating Diffusion Modelsmentioning
confidence: 93%
“…(Ronen et al, 2014), accounting for both the macro- and microscopic curvature of the human corpus callosum, measured a slightly larger D a,‖ (0.51 µm 2 /ms) putting it in the range of 60–70% of aqueous NAA. (Palombo et al, 2017) have also demonstrated diffusion of NAA and other metabolites can be modelled as occurring in long, cylindrical fibers, having a D a,‖ of 0.33 µm 2 /ms. The diffusion weighted signals of other metabolites were also fit well by assuming long cylindrical processes (Najac et al, 2016; Najac et al, 2014; Palombo et al, 2017).…”
Section: Validating Diffusion Modelsmentioning
confidence: 97%
“…At the extreme end of the spectrum, for structures so short that scriptlDδ, entering into regime C, no curvature is tolerated if the tail q −1 is to appear. These considerations will have to be revisited if one measures the diffusion of molecules other than water, due to differences in their diffusion characteristics [48, 49, 50]. …”
Section: Resultsmentioning
confidence: 99%
“…In recent works performed in healthy animals, we have proposed that high diffusion-weighting 85 DW-MRS data primarily reflect the radius of brain cell fibers (dendrites, axons, astrocytic processes…) (Palombo et al, 2017b), while long diffusion times data primarily reflect fiber long-range structure, in particular complexity and length (Palombo et al, 2016). Here we measured signal attenuation of reliable metabolites (CRLB<5 %) up to a diffusion-weighting b=50 ms/µm 2 , at fixed diffusion time t d =53.2 ms, which is well suited to probe restriction in 90 fibers' transverse plane.…”
Section: Dw-mrs Reveals Myo-inositol As a Specific Diffusion Marker Omentioning
confidence: 99%
“…4). High diffusion-weighting data were analyzed using analytical models of diffusion in randomly oriented cylinders (Palombo et al, 2017b), slightly modified to also account for diffusion in spherical soma representing 20% 120 of the total cell volume (Palombo et al, 2018a, b). We extracted fiber radii of 0.58±0.02 µm for the control group versus 0.85±0.02 µm for the CNTF group (+47%), and soma radii of 3.80±0.06 µm for the control group versus 4.66±0.07 µm for the CNTF group (+23%) ( Supplementary Table S2).…”
Section: Diffusion Modeling Allows Quantifying Structural Alterationsmentioning
confidence: 99%